Composite, composition, and cured product
Patent Information
- Application Number
- JP2024099014
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
【0015】 本発明によれば、揮発性有機溶媒を配合しなくとも、熱伝導性に優れ、かつ、流動性の変化が均一であり、絶縁不良の発生を抑制できる複合物及び前記複合物を含む組成物、並びに前記組成物の硬化物を提供することができる。なお、本明細書において「流動性の変化が均一」とは、後述する組成物中の複合物の含有量の増加、複合物や組成物の使用条件及び使用環境などによって、流動性が急激に変化しないことを意味する。すなわち、後述する無機粒子同士の凝集や無機粒子とシリコーン化合物(1)の相分離が起り難いことを意味する。
Smart Images

Figure 2025000596000007 
Figure 2025000596000008 
Figure 2025000596000009
Abstract
Description
[Technical field]
[0001] The present invention relates to composites, compositions and cured products. [Background technology]
[0002] As the performance of electric and electronic devices improves, the power consumption of these heat-generating electronic components is increasing, and the amount of heat generated by these components is also on the rise. Therefore, efficient heat removal from heat-generating electronic components has become an important issue in terms of heat countermeasures for electric and electronic devices. Therefore, a common method for cooling heat-generating electronic components is to press a heat dissipator such as a metal plate or a heat sink onto the surface of the heat-generating electronic component via a thermally conductive sheet or thermally conductive grease, thereby increasing the heat dissipation area. Thermally conductive grease is required to have particularly high thermal conductivity.
[0003] One method for cooling electronic components is to bond a heat sink to the electronic components or the board on which they are mounted. In this case, in order to improve the cooling efficiency, it is not only necessary to improve the performance of the heat sink, but it is also important to promote the thermal conduction of the joint between the heat sink and the electronic components. In other words, it is important to perform surface processing to reduce the unevenness of the joint surface of the heat sink and to increase the area of the joint interface by applying a load to the heat sink. However, these methods are disadvantageous in terms of cost.
[0004] Therefore, a method of improving the cooling efficiency by interposing a thermally conductive layer made of a composition with high heat dissipation between the electronic component and the heat sink has been adopted. For example, a powder called a filler with high thermal conductivity is mixed into a matrix resin such as an epoxy resin or silicone resin to make a composition with high thermal conductivity, and the composition is interposed between the heat sink and the electronic component to improve the cooling efficiency. In this case, a highly insulating material is used as the matrix resin or filler to prevent short circuits of the electronic component.
[0005] As a composition for forming such a thermally conductive layer, a thermally conductive grease in which a thermally conductive filler is filled in silicone oil is generally known. For example, Patent Document 1 discloses a mixture in which a metal compound having high thermal conductivity, such as aluminum nitride or silicon nitride, is added to a hydroxyl-containing organopolysiloxane (silicone oil). Patent Document 2 describes a mixture in which powder of an aluminum nitride sintered body is dispersed in an insulating matrix resin, for example, a polymer material such as silicone oil. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 2-212556 [Patent Document 2] Japanese Patent Application Publication No. 6-209057 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the mixtures described in Patent Documents 1 and 2, silicone oil may bleed out during molding. When silicone oil bleeds out, it remains in the product, and if it adheres to a conductive part (contact point), it may be oxidized and decomposed to become silicon dioxide. When silicon dioxide accumulates in a conductive part, electricity does not flow easily, causing insulation failure, which may induce malfunction of electrical and electronic devices. For this reason, thermal grease is required to have not only thermal conductivity but also the ability to suppress the occurrence of insulation failure.
[0008] By the way, when the filler content in the thermal grease increases, the thermal conductivity improves, but the fluidity tends to change due to phase separation between the filler and silicone oil and the aggregation of the filler. In order to make the fluidity uniform, a diluting solvent may be blended into the thermal grease to suppress the increase in viscosity, but thermal grease containing a volatile organic solvent is difficult to use in areas where the evaporation of the organic solvent would cause problems. For this reason, thermal grease is required to have uniform fluidity without the need to add volatile organic solvents.
[0009] An object of the present invention is to provide a composite that has excellent thermal conductivity and exhibits uniform change in fluidity even without the incorporation of a volatile organic solvent, and that can suppress the occurrence of insulation defects, a composition containing the composite, and a cured product of the composition. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors conducted intensive research to achieve the above-mentioned object and as a result discovered that the above-mentioned object can be achieved by surface-treating inorganic particles with a surface modifier containing a silicone compound having a specific structure, thereby completing the present invention.
[0011] That is, the present invention relates to the following items [1] to
[14] . [1] A composite material in which inorganic particles are surface-treated with a surface modifier containing a silicone compound represented by the following general formula (1): The silicone compound is bonded to the inorganic particles.
[0012] [ka]
[0013] In the general formula (1), X is a functional group containing one or more of an alkyl group having 2 to 6 carbon atoms, a hydroxyl group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, and an isocyanate group; R 1 and R 2 each independently represents an alkyl group, a phenyl group, an alkenyl group, a hydroxy group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; R a and R b each independently represents an alkyl group, a phenyl group, an alkenyl group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; Z 1 ~Z 3 are each independently a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a halogen atom, or a carboxy group; Z 1 ~Z 3 At least one of these is a hydrogen atom, an alkoxy group, a hydroxy group, a halogen atom or a carboxy group, and n is an integer of 1 to 10,000. [2] Z in the general formula (1) 1 ~Z 3 At least one of the above is a hydrogen atom.
[0014] [3] The composite of [1] or [2] above, which is used as a heat conduction material, an optical material, or a heat dissipation material in semiconductor manufacturing. [4] The composite of any one of the above [1] to [3], wherein the inorganic particles have an average primary particle size of 0.0001 to 100 μm. [5] The composite according to any one of [1] to [4] above, wherein the content of the solvent in the composite is 0 to 10 mass % based on the total mass of the composite. [6] The composite of any of the above [1] to [5], wherein a volume ratio of the surface modifier to the inorganic particles (the surface modifier / the inorganic particles) is 0.1 to 100. [7] The composite of any one of the above [1] to [6], wherein the surface modifier has one or more polymerizable groups. [8] X and R in the above general formula 1 , R 2 , R a and R b At least one of the above is a polymerizable group or a functional group containing a polymerizable group. [9] X and R in the above general formula 1 , R 2 , R a and R b at least one of the groups selected from the group consisting of a hydroxyl group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, and an isocyanate group.
[10] The composite of any one of the above [1] to [9], wherein the weight average molecular weight of the silicone compound is 550 to 100,000.
[11] The composite of any one of the above [1] to
[10] , wherein the surface modifier consists solely of the silicone compound.
[12] The composite of any one of [1] to
[11] above, having a thermal conductivity of 0.3 to 10 W / (m K).
[13] A composition comprising any one of the compounds [1] to
[12] above.
[14] A cured product of the composition according to
[13] . Effect of the Invention
[0015] According to the present invention, it is possible to provide a composite having excellent thermal conductivity and uniform change in fluidity, which can suppress the occurrence of insulation failure, even without blending a volatile organic solvent, a composition containing the composite, and a cured product of the composition. In this specification, "uniform change in fluidity" means that the fluidity does not change suddenly due to an increase in the content of the composite in the composition described below, the use conditions and the use environment of the composite or composition, etc. In other words, it means that aggregation between inorganic particles and phase separation between the inorganic particles and the silicone compound (1), which will be described later, is unlikely to occur. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a graph showing viscosity versus shear rate in Example 1. [Diagram 2] FIG. 13 is a graph showing viscosity versus shear rate in Example 2. [Diagram 3] FIG. 13 is a graph showing viscosity versus shear rate in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in further detail below by presenting preferred embodiments of the invention. However, the following description is one example of an embodiment of the present invention, and the present invention is not limited to the contents described below as long as it does not go beyond the gist of the invention. In this specification, the use of "to" indicating a range of values means that the values before and after it are included as the lower limit and upper limit.
[0018] [Composite] The composite of the present invention is an inorganic particle-silicone composite in which the inorganic particles are surface-treated with a surface modifier containing the silicone compound shown below. The silicone compound is bonded to the inorganic particles. By bonding the silicone compound to the inorganic particles, the silicone compound is less likely to bleed out during molding. Therefore, the silicone compound is less likely to change to silicon dioxide within the product, and the occurrence of insulation defects can be suppressed. In the present invention, the phrase "a silicone compound is bonded to an inorganic particle" means that the silicone compound is bonded to the surface of the inorganic particle by a covalent bond, a coordinate bond, an ionic bond, or a hydrogen bond.
[0019] <Inorganic particles> The inorganic particles include inorganic oxide particles. Examples of inorganic oxide particles include oxides such as silver, copper, aluminum, and iron-based metal fillers, aluminum nitride, boron nitride, silicon carbide, silicon nitride, silica, and diamond; oxides such as zinc oxide, zirconium oxide, magnesium oxide, aluminum oxide, beryllium oxide, titanium oxide, silicon oxide, iron oxide, copper oxide, yttrium oxide, niobium oxide, molybdenum oxide, indium oxide, tin oxide, tantalum oxide, tungsten oxide, lead oxide, bismuth oxide, cerium oxide, antimony oxide, and germanium oxide; and composite oxides such as tin-doped indium oxide (ITO) and yttria-stabilized zirconia (YSZ). Furthermore, examples of inorganic particles that may be used include metal fillers such as silver, copper, aluminum, and iron; and compounds such as aluminum nitride, boron nitride, silicon carbide, silicon nitride, silica, and diamond.
[0020] As the inorganic particles, inorganic oxide particles are preferred from the viewpoint of being more easily bonded to the silicone compound (1) described below. Among them, oxides such as aluminum nitride, boron nitride, and silicon carbide; and oxides such as zinc oxide, zirconium oxide, titanium oxide, and aluminum oxide are particularly preferred from the viewpoint of high thermal conductivity. The inorganic particles may be used alone or in any combination of two or more kinds in any ratio.
[0021] The average primary particle size of the inorganic particles is preferably 0.0001 to 100 μm, more preferably 0.01 to 100 μm, even more preferably 0.01 to 10 μm, and particularly preferably 0.01 to 1 μm. If the average primary particle size of the inorganic particles is equal to or greater than the lower limit, the crystallinity is increased, and the specific surface area is small, so that the amount of surface modifier that covers the inorganic particles is reduced, resulting in high thermal conductivity. If the average primary particle size of the inorganic particles is equal to or less than the upper limit, the fluidity of the composite is improved, the composite is less likely to aggregate, and the composite can be handled in the same manner as general-purpose silicone grease. The term "average primary particle size" refers to the particle size at a cumulative 50% (D50: median size) in the volume-based particle size distribution measured by dynamic light scattering (DLS).
[0022] The inorganic particles may be commercially available or may be synthesized. Methods for producing inorganic oxide particles include a top-down method (breakdown method) and a bottom-up method (build-up method). The top-down method is a method in which aggregates of several micrometers are mechanically crushed and broken down using a grinder or other device to obtain fine particles. The bottom-up method is a method for obtaining fine particles by chemically synthesizing raw materials, such as a gas-phase method or a liquid-phase method. Among these, the bottom-up method is preferred, and from the viewpoint of easily obtaining nanoparticles with a uniform particle size, a method of chemically producing the nanoparticles from raw materials by a liquid phase method is more preferred.
[0023] <Surface modifier> The surface modifier includes a silicone compound represented by the following general formula (1) (hereinafter, also referred to as "silicone compound (1)"). The surface modifier may consist of only the silicone compound (1), or may contain components other than the silicone compound (1) (hereinafter, also referred to as "other components"). It is preferable that the surface modifier consists of only the silicone compound (1) in order to maintain good dispersibility when dispersing the composite in the matrix resin described below.
[0024] (Silicone Compound (1)) The silicone compound (1) is a compound represented by the following general formula (1).
[0025] [ka]
[0026] In the general formula (1), X is a functional group containing one or more of an alkyl group having 2 to 6 carbon atoms, a hydroxyl group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, and an isocyanate group; R 1 and R 2 each independently represents an alkyl group, a phenyl group, an alkenyl group, a hydroxy group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; R a and R b each independently represents an alkyl group, a phenyl group, an alkenyl group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; Z 1 ~Z 3 are each independently a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a halogen atom, or a carboxy group; Z 1 ~Z 3 At least one of these is a hydrogen atom, an alkoxy group, a hydroxy group, a halogen atom or a carboxy group, and n is an integer of 1 to 10,000.
[0027] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, and a butyl group. Examples of the alkenyl group include a vinyl group and an allyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0028] The functional group in X may be an alkyl group having 2 to 6 carbon atoms, a hydroxyl group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, or an isocyanate group, or may have a moiety other than these groups. For example, the functional group containing an isocyanate group is an isocyanate group (O=C=N-) or an O=C=N-CH 2 -CH 2 -OC(=O)-CH 2 - etc.
[0029] R 1 and R 2 may be the same or different, but is preferably the same. R a and R b may be the same or different, but are preferably the same. When n is an integer of 2 or more, a Although they may be the same or different, it is preferable that they are the same. b may be the same or different, but is preferably the same. a and R b It is more preferable that they are the same.
[0030] Z 1 ~Z 3 may be the same or different, but at least one of them is a hydrogen atom, an alkoxy group, a hydroxyl group, a halogen atom, or a carboxy group. When the inorganic particles are inorganic oxide particles, Z 1 ~Z 3 At least one of these is a hydrogen atom, an alkoxy group, a hydroxy group, a halogen atom or a carboxy group, and thus the inorganic oxide particles are strongly bonded to the hydroxy groups on the surface thereof by hydrolysis, condensation or hydrogen bonding.
[0031] n is an integer of 1 to 10,000, preferably an integer of 1 to 1,000, and more preferably an integer of 3 to 100. When the value of n is equal to or greater than the lower limit, the fluidity of the molecular chain itself can impart fluidity to the material. When the value of n exceeds the upper limit, the long chain length causes significant steric hindrance, making it difficult for the silicone compound (1) to bond efficiently with the inorganic particles. Furthermore, regardless of whether the chain length is long or short, the number of surface modifiers per unit area of the particle is the same, and the longer the chain length, the smaller the relative volume fraction of the inorganic particles in the composite, and the lower the refractive index of the composite tends to be.
[0032] When the composite is used without curing, from the viewpoint of the stability of the raw materials when synthesizing the silicone compound (1), X is preferably an alkyl group having 2 to 6 carbon atoms, more preferably an alkyl group having 2 to 4 carbon atoms. In addition, the increase in the viscosity of the composite can be suppressed, making it easy to handle. In addition, from the viewpoint of the stability of the raw materials when synthesizing the silicone compound (1), R 1 , R 2 , R a and R b At least one of R is preferably an alkyl group, and more preferably a methyl group. 1 , R 2 , R a and R b It is preferable that all of the groups are alkyl groups, and more preferable that all of the groups are methyl groups.
[0033] When the composite is used after curing, it can be easily cured depending on the location where the composite is used, and a cured product of the composition described later can be easily obtained. 1 , R 2 , R a and R b Among these, at least one is preferably a polymerizable group. That is, it is preferable that the silicone compound (1) has one or more polymerizable groups. In particular, X is preferably a polymerizable group or a functional group containing a polymerizable group, more preferably a functional group containing a hydroxyl group, an acrylic group, or a methacrylic group, and further preferably a hydroxyl group, an acrylic group, or a methacrylic group. Here, the "polymerizable group" refers to a hydroxy group, an alkoxy group, an acrylic group, a methacrylic group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, or an isocyanate group. Among these, from the viewpoint of easy polymerization, a hydroxy group, an alkoxy group, an acrylic group, a methacrylic group, and a thiol group are preferred, and a hydroxy group, an acrylic group, and a methacrylic group are more preferred.
[0034] Also, Z 1 ~Z 3 At least one of these is preferably a hydrogen atom, an alkoxy group, or a hydroxy group, and more preferably one is a hydrogen atom or a hydroxy group and the remaining two are alkyl groups.
[0035] The weight average molecular weight of the silicone compound (1) is preferably 550 to 100000, more preferably 600 to 80000, further preferably 650 to 75000, and particularly preferably 700 to 60000. When the weight average molecular weight of the silicone compound (1) is within the above range, the fluidity of the composite is further improved. The number average molecular weight of the silicone compound (1) is preferably 250 to 90000, more preferably 300 to 85000, further preferably 350 to 80000, and particularly preferably 400 to 75000. When the number average molecular weight of the silicone compound (1) is within the above range, the fluidity of the composite is further improved. The weight average molecular weight and number average molecular weight of the silicone compound (1) are values calculated as polystyrene standards measured by gel permeation chromatography (GPC).
[0036] The silicone compound (1) may be a commercially available product or may be synthesized. Examples of methods for producing the silicone compound (1) include a method in which chlorosilane, dialkoxysilane, diphenoxysilane, or diacyloxysilane is subjected to hydrolysis and polycondensation, and a method in which cyclic siloxane is subjected to ring-opening polymerization.
[0037] When silicone compound (1) is produced by the method of hydrolyzing and polycondensing the above-mentioned chlorosilanes, dialkoxysilanes, diphenoxysilanes, or diacyloxysilanes, it is possible to provide reactive sites, and therefore it is preferable to produce silicone compound (1) from the compounds shown below or polycondensates of their hydrolysates. Dimethyldimethoxysilane, phenylmethyldimethoxysilane, dimethyldiethoxysilane, phenylmethyldiethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropylmethyldiethoxysilane, dimethyldiacetoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane, γ-aminopropylmethyl Dimethoxysilane, γ-aminopropylmethyldiethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, divinyldimethoxysilane, divinyldiethoxysilane, glycidoxymethylmethyldimethoxysilane, glycidoxymethylmethyldiethoxysilane, α-glycidoxyethylmethyldimethoxysilane, α-glycidoxyethylmethyldiethoxysilane, β-glycidoxyethylmethyldimethoxysilane, β-glycidoxyethylmethyldiethoxysilane, α-glycidoxyethylmethyldiethoxysilane α-glycidoxypropylmethyldimethoxysilane, α-glycidoxypropylmethyldiethoxysilane, β-glycidoxypropylmethyldimethoxysilane, β-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldipropoxysilane, γ-glycidoxypropylmethyldibutoxysilane, γ-glycidoxypropylmethyldimethoxyethoxysilane, γ-glycidoxypropylmethyldipropoxysilane Dialkoxysilanes, diphenoxysilanes, and diacyloxysilanes such as propylmethyldiphenoxysilane, γ-glycidoxypropylmethyldiacetoxysilane, γ-glycidoxypropylethyldimethoxysilane, γ-glycidoxypropylethyldiethoxysilane, γ-glycidoxypropylvinyldimethoxysilane, γ-glycidoxypropylvinyldiethoxysilane, γ-glycidoxypropylphenyldimethoxysilane, and γ-glycidoxypropylphenyldiethoxysilane.
[0038] Among these, from the viewpoint of further improving fluidity, it is more preferable to produce the silicone compound (1) from the compounds shown below or polycondensates of their hydrolysates. Dimethyldimethoxysilane, phenylmethyldimethoxysilane, dimethyldiethoxysilane, phenylmethyldiethoxysilane, gamma-mercaptopropylmethyldimethoxysilane, gamma-mercaptopropylmethyldiethoxysilane, gamma-aminopropylmethyldimethoxysilane, gamma-aminopropylmethyldiethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, divinyldimethoxysilane, divinyldiethoxysilane, etc.
[0039] When the silicone compound (1) is produced by the above-mentioned method of ring-opening polymerization of a cyclic siloxane, the ring-opening polymerization is usually carried out in the presence of an initiator and a terminator. Examples of cyclic siloxanes include those having a substituent such as hexamethylcyclotrisiloxane, hexaphenylcyclotrisiloxane, octamethylcyclotetrasiloxane, and octaphenylcyclotetrasiloxane. Among these, hexamethylcyclotrisiloxane and octamethylcyclotetrasiloxane are preferred from the viewpoint of lowering the viscosity of the resulting composite. Examples of the initiator include organolithium compounds such as n-butyllithium, sec-butyllithium, etc. Among these, n-butyllithium and sec-butyllithium are preferred from the viewpoint of the stability of the organolithium compound. Examples of the terminator include monochlorosilanes such as trimethylchlorosilane, vinyldimethylchlorosilane, allyldimethylchlorosilane, dimethylchlorosilane, phenylmethylchlorosilane, diphenylchlorosilane, diisopropylchlorosilane, and γ-methacryloxypropyldimethylchlorosilane. Among these, vinyldimethylchlorosilane, allyldimethylchlorosilane, dimethylchlorosilane, phenylmethylchlorosilane, diphenylchlorosilane, and diisopropylchlorosilane are preferred from the viewpoint of imparting to the silicone compound (1) a functional group that bonds with a hydroxy group on the surface of an inorganic particle or a functional group that can be converted by chemical reaction into a functional group that bonds with a hydroxy group on the surface of an inorganic particle.
[0040] The silicone compound (1) may be used alone or in combination of two or more kinds in any ratio. The content of the silicone compound (1) in the surface modifier is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the surface modifier, and may be 100% by mass.
[0041] (Other ingredients) The surface modifier of the present invention may contain other components within the range that does not impair the effects of the present invention. Examples of other components include organotrialkoxysilanes and compounds having a polymerizable group other than the silicone compound (1). The other components may be used alone or in any combination of two or more kinds in any ratio. Examples of organotrialkoxysilanes include methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, γ-chloropropyltrimethoxysilane, γ-chloropropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane. Among these, X, R 1 , R 2 , R a and R b In the case of using a silicone compound (1) in which the group is not a polymerizable group, from the viewpoints that the composite can be easily cured depending on the location where it is used when it is cured for use and that a cured product of the composition described below can be easily obtained, preferred are γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane. The content of organotrialkoxysilanes in the surface modifier is preferably 40 mass % or less, more preferably 30 mass % or less, and even more preferably 20 mass % or less, based on the total mass of the surface modifier.
[0042] <Ratio> The volume ratio of the surface modifier to the inorganic particles (surface modifier / inorganic particles) is preferably 0.1 to 100, more preferably 1 to 30, and even more preferably 1 to 20. When the volume ratio is equal to or greater than the lower limit, the flowability of the composite is improved, the composite is less likely to aggregate, and the composite can be handled in the same manner as general-purpose silicone grease. In addition, the dispersibility when dispersing the composite in a matrix resin described below is improved, and the flowability of the composition is also improved. When the volume ratio is equal to or less than the upper limit, the thermal conductivity of the composite is improved.
[0043] <Physical Properties> (Average primary particle size) The average primary particle size of the composite is preferably 0.001 to 1000 μm, more preferably 0.005 to 500 μm, even more preferably 0.005 to 100 μm, and particularly preferably 0.01 to 10 μm. If the average primary particle size of the composite is equal to or greater than the lower limit, the thermal conductivity of the composite is further improved. If the average primary particle size of the composite is equal to or less than the upper limit, the flowability of the composite is further improved, the composite is less likely to aggregate, and the composite can be handled in the same manner as general-purpose silicone grease.
[0044] (Amount of solvent) The composite of the present invention has a uniform change in fluidity. Therefore, the composite of the present invention does not need to be blended with an organic solvent for adjusting the viscosity. That is, the composite of the present invention can be in an embodiment that does not substantially contain a volatile organic solvent. Specifically, the content of the solvent in the composite (solvent amount) can be 0 to 10 mass % or less with respect to the total mass of the composite. The solvent amount is more preferably 0 to 1 mass %, further preferably 0 to 0.1 mass %, and particularly preferably 0 mass %. When the solvent amount is equal to or less than the upper limit, the production cost and the environmental load can be reduced. Furthermore, since the composite of the present invention has a low viscosity, there is no need to incorporate a diluent monomer.
[0045] (Thermal Conductivity) The composite of the present invention contains the inorganic particles described above, and therefore has excellent thermal conductivity. Specifically, the thermal conductivity of the composite is likely to be 0.3 W / (m·K) or more. The thermal conductivity of the composite is preferably 0.3 to 10 W / (m·K). The thermal conductivity of the composite can be measured by the method described in the Examples.
[0046] (light transparency) In the composite of the present invention, the inorganic particles are bonded to the silicone compound (1), and therefore the composite has better light transmittance than a simple mixture of the inorganic particles and the silicone compound (1). Specifically, the haze of the composite is preferably 15% or less. The haze, which is an indicator of the light transmittance of the composite, can be measured by the method described in the Examples.
[0047] The reason why the composite of the present invention has excellent light transmittance is not clear, but is thought to be as follows. That is, in a simple mixture of inorganic particles and silicone compound (1), the inorganic particles form aggregates and scatter light, whereas in the composite of the present invention, the inorganic particles are treated with silicone compound (1), and thus aggregation of the inorganic particles is suppressed.
[0048] (viscosity) The viscosity of the composite at 25°C is preferably 1000 Pa·s or less, more preferably 750 Pa·s or less, and even more preferably 500 Pa·s or less. The viscosity of the composite at 25°C is preferably 0 Pa·s or more, and more preferably 0.001 Pa·s or more. If the viscosity of the composite is equal to or less than the upper limit, the composite can be handled in the same way as general-purpose silicone grease, and the composite can be molded and cured independently. In addition, it is easy to mix and disperse the composite into other inorganic particles. The lower limit and the upper limit of the viscosity of the composite can be combined in any desired manner. For example, the viscosity of the composite at 25° C. is preferably 0 to 1000 Pa·s, more preferably 0.001 to 750 Pa·s, and even more preferably 0.001 to 500 Pa·s. The viscosity of the composite was measured at 25°C and a shear rate of 0.1 sec. -1 or 1.0sec -1 , preferably 1.0 sec -1 The values were measured using a rheometer under the following conditions. The viscosity of the composite can be easily controlled, for example, by adjusting the value of n in the general formula (1). Specifically, the viscosity of the composite tends to increase as the value of n increases. If the value of n is within the above range, the viscosity of the composite can be easily controlled to the range described below.
[0049] <Manufacturing method> The composite can be obtained by heating and reacting the inorganic particles with the surface modifier in an organic solvent, and then removing the organic solvent. Silicone Compound (1) Z 1 ~Z 3 When at least one of is a hydrogen atom, the reaction is preferably carried out in the presence of a basic compound. When the reaction is carried out in the presence of a basic compound, the basic compound is removed after the reaction using an acidic ion exchange resin or the like. The basic compound is preferably an amine compound. Examples of the amine compound include alkylamine compounds such as N,N-diethylhydroxylamine and triethylamine. Among these, N,N-diethylhydroxylamine is more preferable.
[0050] Examples of the organic solvent include propylene glycol methyl ether acetate, ethyl acetate, butyl acetate, methyl ethyl ketone, and alcohol. The reaction temperature is preferably from 30 to 250°C, more preferably from 35 to 200°C, and further preferably from 40 to 150°C. The reaction time is preferably from 1 to 24 hours, more preferably from 3 to 15 hours, and further preferably from 5 to 10 hours.
[0051] <Action and effect> The composite of the present invention is an inorganic particle-silicone composite in which the inorganic particles are surface-treated with a surface modifier containing the above-mentioned silicone compound (1) to bond the silicone compound (1) to the surface of the inorganic particles, and has excellent thermal conductivity and a uniform change in fluidity. The effect of the present invention is not clear, but is presumed to be as follows. By treating inorganic particles with a surface modifier containing a silicone compound (1), it is possible to suppress aggregation of inorganic particles, thereby reducing interactions between particles and making the change in fluidity uniform. In addition, since the silicone compound (1) is bonded to the inorganic particles, the silicone compound (1) is less likely to bleed out during molding. Therefore, the silicone compound (1) is less likely to change to silicon dioxide inside the product, so the composite of the present invention can suppress the occurrence of insulation failure. In addition, the composite of the present invention does not require the incorporation of an organic solvent or diluting monomer for adjusting the viscosity, and can be substantially free of volatile organic solvents. This reduces the manufacturing cost and the environmental load. The composite of the present invention can also be suitably used in areas where problems occur due to the evaporation of organic solvents.
[0052] <Application> The composite of the present invention can be suitably used as a thermal grease for heat conductive members, optical members, and heat dissipation materials in semiconductor manufacturing.
[0053] [Composition] The composition of the present invention comprises the composite of the present invention described above. The composite of the present invention can be handled in the same manner as a general-purpose silicone grease, and can be molded and cured by itself. In particular, if the surface modifier in the composite has one or more of the above-mentioned polymerizable groups, the composite can be easily cured by itself. Therefore, the composition may be composed of only the composite. Furthermore, the composition may contain, in addition to the composite, components other than the composite (hereinafter also referred to as "optional components") within a range that does not impair the effects of the present invention.
[0054] Examples of optional components include a matrix resin, a compound that generates radicals by heat (hereinafter also referred to as a "thermal radical generator"), and a compound that generates radicals by light (hereinafter also referred to as a "photoradical generator"). In addition, from the viewpoint of suppressing insulation failure, it is preferable that the composition does not substantially contain silicone oil as an optional component. Here, "substantially does not contain" means that silicone oil is not actively blended into the composition, except for silicone oil that is unintentionally contained. Furthermore, as described above, since the composite of the present invention can be in an embodiment that is substantially free of volatile organic solvents, it is preferable that the composition of the present invention also is substantially free of volatile organic solvents.
[0055] Examples of the matrix resin include epoxy resin, acrylic resin, and silicone resin. The matrix resin may be used alone or in any combination of two or more kinds in any ratio.
[0056] When the composition contains a matrix resin, the content of the composite is preferably 100 to 50,000 parts by mass, more preferably 1,000 to 20,000 parts by mass, and even more preferably 5,000 to 10,000 parts by mass, relative to 100 parts by mass of the matrix resin. When the content of the composite is equal to or more than the lower limit, sufficient thermal conductivity can be obtained. When the content of the composite is equal to or less than the upper limit, an increase in the viscosity of the composition can be further suppressed.
[0057] When the composite in the composition contains a compound containing an acrylic group or a methacrylic group and a cured product described below is to be obtained from the composition, the composition needs to contain a thermal radical generator or a photoradical generator. The thermal radical generator is not particularly limited as long as it radically polymerizes unsaturated bond-containing groups by heat, and any conventionally known thermal radical polymerization initiator can be selected. Examples of the thermal radical polymerization initiator include organic peroxides and azo compounds. Examples of organic peroxides include 2,4-dichlorobenzoyl peroxide, t-butyl peroxypivalate, o-methylbenzoyl peroxide, bis-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, t-butylperoxy-2-ethylhexanoate, cyclohexanone peroxide, benzoyl peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, lauroyl peroxide, diisopropylbenzene hydroperoxide, t-butyl hydroperoxide, and di-t-butyl peroxide. Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile). Among these, benzoyl peroxide, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile) are preferred. The thermal radical polymerization initiators can be used alone or in combination of two or more kinds. In order to obtain good curability of the composition, the content of the thermal radical polymerization initiator is preferably 0.001 to 15% by mass relative to 100% by weight of the composition.
[0058] The photoradical generator is not particularly limited as long as it can radically polymerize unsaturated bond-containing groups with each other by light, and any of the conventionally known photoradical polymerization initiators can be selected. Examples of photoradical polymerization initiators include thioxanthones such as benzophenone, 4,4-bis(diethylamino)benzophenone, 2,4,6-trimethylbenzophenone, methyl orthobenzoyl benzoate, 4-phenylbenzophenone, t-butylanthraquinone, 2-ethylanthraquinone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, and the like; acetophenones such as diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, and the like. -one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, etc., benzoin ethers; benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, etc., acylphosphine oxides; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc., other compounds; methylbenzoyl formate, 1,7-bisacridinylheptane, 9-phenylacridine, etc. Among these, thioxanthones, acetophenones, benzoin ethers, and acylphosphine oxides are preferred.The photoradical polymerization initiator may be used alone or in combination of two or more kinds. In order to obtain good curability of the composition, the content of the photoradical polymerization initiator is preferably 0.1 to 15% by mass relative to 100% by weight of the composition.
[0059] A composition containing the composite and any optional component can be obtained, for example, by stirring and mixing the composite and the optional component with a commonly used stirrer.
[0060] The composition of the present invention contains the above-mentioned composite of the present invention, and therefore has excellent thermal conductivity. The composition of the present invention can be suitably used as a thermal grease for heat conductive members, optical members, and heat dissipation materials in semiconductor manufacturing.
[0061] [Cured product] The cured product of the present invention is a cured product of the composition of the present invention. The cured product of the present invention is suitable as, for example, an optical component. The cured product of the present invention can be obtained by thermally curing or photocuring the composition of the present invention. The composite contained in the composition to be cured is preferably an inorganic particle surface-treated with a surface treatment agent containing a polymerizable group. The surface treatment agent containing a polymerizable group is one in which at least one of the above-mentioned silicone compound (1) and other components has a polymerizable group. In particular, X and R in the general formula (1) 1 , R 2 , R a and R b In a preferred embodiment, the inorganic particles are surface-treated with a surface treatment agent containing a silicone compound (1), at least one of which is a polymerizable group or a functional group containing a polymerizable group.
[0062] When the polymerizable groups in the composite are hydroxy groups, curing is possible simply by heating. The heat curing temperature is preferably from 40 to 200°C, more preferably from 80 to 150°C, and further preferably from 90 to 130°C. The heat curing time is preferably from 1 to 24 hours, more preferably from 3 to 15 hours, and further preferably from 5 to 10 hours.
[0063] When the polymerizable group in the composite is an acrylic group or a methacrylic group, curing is possible by radical polymerization using the above-mentioned thermal radical generator and photoradical generator. For the light irradiation, active energy rays such as ultraviolet rays, electron beams, X-rays, infrared rays, and visible light can be used. The cumulative radiation dose during curing is 1 to 40,000 mJ / cm 2 is preferable, and 10 to 20,000 mJ / cm 2 More preferably, 100 to 10,000 mJ / cm 2 is more preferred. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0065] [Measurement and evaluation method] <Measurement of average primary particle size> A particle size distribution meter (MicrotracBEL, product name "Nanotrac Wave") was used to measure the volumetric particle size distribution of the inorganic particles or composites, and the particle diameter at the cumulative 50% (D50: median diameter) was calculated as the average primary particle diameter of the inorganic particles or composites.
[0066] <Evaluation of changes in liquidity> The viscosity of the composite or silicone compound (1) was measured using a rheometer (manufactured by Thermo Fischer, product name "HAAKE MARS III"), and the fluidity was evaluated according to the following evaluation criteria. The viscosity of the composite was measured at a temperature of 25°C and a shear rate of 1.0 sec. -1 The viscosity of silicone compound (1) was measured at a temperature of 25°C and a shear rate of 10 sec. -1 The measurements were performed under the following conditions.
[0067] <Evaluation of thermal conductivity> The thermal conductivity of the composite or silicone compound (1) was measured using a thermal property measuring device (manufactured by Mentor Graphics Corporation, product name "T3Ster DynTIM Tester"), and the thermal conductivity was evaluated according to the following evaluation criteria. (Evaluation Criteria) 〇: Thermal conductivity is 0.30 W / (m K) or higher, and the material has excellent thermal conductivity. ×: Thermal conductivity is less than 0.30 W / (m·K) and the thermal conductivity is poor.
[0068] <Evaluation of light transmittance> The haze of the composite was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "HazeMeter NDH7000SP2") in accordance with JIS K 7136:2000. The sample was sandwiched between glass plates during measurement. For the blank, two glass plates were stacked with the sample sandwiched between them. (Haze evaluation criteria) ◯: Haze is 15% or less, and light transmittance is excellent. ×: Haze is higher than 15%, and light transmittance is poor.
[0069] [Example 1] Propylene glycol methyl ether acetate was added as a solvent to titanium oxide having an average primary particle size of 48 nm as inorganic particles to prepare a dispersion liquid with a titanium oxide concentration of 5 mass %. The resulting dispersion was mixed with a polydimethylsiloxane having a weight average molecular weight (Mw) of 550 and silanol groups at both ends (X and Z in the above general formula (1)) as a surface modifier. 2 is a hydroxy group, and R 1 , R 2 , R a , R b , Z 1 and Z 3Silicone compound (1) in which n is a methyl group and n is 3 was added so that the surface modifier / inorganic particles ratio was 15 (volume ratio), and the mixture was heated and stirred at 120° C. for 7 hours. The solvent was then removed to obtain a composite in which the inorganic particles were surface-treated with the surface modifier, the average primary particle size was 300 nm, and the solvent amount was 0 mass %. The obtained composite was evaluated for thermal conductivity and change in fluidity. The evaluation of thermal conductivity is shown in Table 1, and the evaluation of change in fluidity is shown in Figure 1.
[0070] [Comparative Example 1] The thermal conductivity was evaluated for the silicone compound (1) which was the surface modifier used in Example 1. The results are shown in Table 1.
[0071] [Table 1]
[0072] As is clear from the results in Table 1, the composite obtained in Example 1 had excellent thermal conductivity. Furthermore, as is clear from Figure 1, the fluidity of the composite obtained in Example 1 changed constantly even when the shear rate changed, and the change in fluidity was uniform. In contrast, the silicone compound (1) alone had poor thermal conductivity.
[0073] [Example 2] 2-butanone (methyl ethyl ketone) was added as a solvent to silica having an average primary particle size of 12 nm as inorganic particles to prepare a dispersion liquid with a silica concentration of 10 mass %. The resulting dispersion was treated with a surface modifier having a number average molecular weight (Mn) of 800 to 900, 2 is a hydrogen atom, and R 1 , R 2 , R a , R b , Z 1 and Z 3A silicone compound (1) in which n is a methyl group and n is 8 to 10 was added so that the surface modifier / inorganic particles was 2 (volume ratio), and 0.1 mass % of N,N-diethylhydroxylamine was added to the silicone compound (1), followed by heating and stirring at 60° C. for 6 hours. Thereafter, the N,N-diethylhydroxylamine was removed with an acidic ion exchange resin, the acidic ion exchange resin was filtered off, and the solvent was removed under reduced pressure to obtain a composite in which the inorganic particles were surface-treated with the surface modifier, the average primary particle size was 12 nm, and the solvent amount was 0 mass %. The resulting composite was evaluated for changes in thermal conductivity, light transmittance, and fluidity. The sample for evaluating light transmittance was prepared by placing a 0.5 μm thick, 0.5 cm wide silicone spacer on the edge of a 5 cm square glass plate, dripping the solution obtained after filtering out the acidic ion exchange resin onto the area surrounded by the spacer, and air drying at room temperature. The results of thermal conductivity and light transmittance are shown in Table 2, and the changes in fluidity are shown in Figure 2.
[0074] [Comparative Example 2] In the same manner as in Example 1, a dispersion liquid with a silica concentration of 10 mass % was prepared. The resulting dispersion was added with a surface modifier having a number average molecular weight (Mn) of 800 to 900, 2 is a hydrogen atom, and R 1 , R 2 , R a , R b , Z 1 and Z 3 Silicone compound (1) in which is a methyl group and n is 8 to 10 was added so that the surface modifier / inorganic particles was 2 (volume ratio). The solvent was then removed under reduced pressure to obtain a simple mixture of inorganic particles and silicone compound (1) in which the inorganic particles and silicone compound (1) were not bonded to each other. The average primary particle size of the mixture was 12 nm, and the amount of solvent was 0 mass%. The resulting mixture was evaluated for changes in thermal conductivity, light transmittance, and fluidity in the same manner as in Example 2. The results of thermal conductivity and light transmittance are shown in Table 2, and the changes in fluidity are shown in FIG.
[0075] [Table 2]
[0076] As is clear from the results in Table 2, the composite obtained in Example 2 was excellent in thermal conductivity and light transmittance. Furthermore, as is clear from Figure 2, the fluidity of the composite obtained in Example 2 changed constantly even when the shear rate changed, and the change in fluidity was uniform. In contrast, the results in Table 2 show that the mixture obtained in Comparative Example 2 had excellent thermal conductivity but poor light transmittance. Also, the results in Fig. 3 show that the mixture obtained in Comparative Example 2 tended to have a sudden change in fluidity when the shear rate changed, and the change in fluidity was not uniform. The reason why Example 2 had excellent light transmittance and uniform change in fluidity is presumably because the silicone compound was bonded to the surface of the inorganic particles, thereby suppressing aggregation between the inorganic particles and phase separation between the inorganic particles and the silicone compound. In Comparative Example 2, the silicone compound was a mixture of inorganic particles, and the silicone compound was not bonded to the surface of the inorganic particles. As a result, the inorganic particles aggregated together and there was phase separation between the inorganic particles and the silicone compound. This is presumably why the light transmittance was poor and the change in fluidity was non-uniform.
Claims
1. A composite material in which inorganic particles are surface-treated with a surface modifier containing a silicone compound represented by the following general formula (1), The silicone compound is bonded to the inorganic particles. 【Chemistry 1】 In the general formula (1), X is a functional group containing one or more of an alkyl group having 2 to 6 carbon atoms, a hydroxyl group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, and an isocyanate group; R 1 and R 2 each independently represents an alkyl group, a phenyl group, an alkenyl group, a hydroxy group, an alkoxy group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; R a and R b each independently represents an alkyl group, a phenyl group, an alkenyl group, an acryl group, a methacryl group, an epoxy group, a styryl group, an amino group, a ureido group, a thiol group, a mercaptopropyl group, or an isocyanate group; Z 1 ~Z 3 are each independently a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a halogen atom or a carboxy group; Z 1 ~Z 3 At least one of these is a hydrogen atom, an alkoxy group, a hydroxy group, a halogen atom or a carboxy group, and n is an integer of 1 to 10,000.
2. Z in the general formula (1) 1 ~Z 3 The compound of claim 1 , wherein at least one of the groups is a hydrogen atom.
3. The composite according to claim 1 or 2, which is used as a heat conductive member, an optical member, or a heat dissipation material in semiconductor manufacturing.
4. 3. The composite according to claim 1, wherein the inorganic particles have an average primary particle size of 0.0001 to 100 μm.
5. The composite according to claim 1 or 2, wherein the content of the solvent in the composite is 0 to 10% by weight based on the total weight of the composite.
6. 3. The composite according to claim 1, wherein a volume ratio of the surface modifier to the inorganic particles (the surface modifier / the inorganic particles) is 0.1 to 100.
7. The composite of claim 1 or 2, wherein the surface modifier has one or more polymerizable groups.
8. 3. The composite of claim 1 or 2, wherein the weight average molecular weight of the silicone compound is 550 to 100,000.
9. 3. The composite of claim 1 or 2, wherein the surface modifier consists solely of the silicone compound.
10. 3. The composite of claim 1 or 2, having a thermal conductivity of 0.3 to 10 W / (m·K).
11. A composition comprising the compound of claim 1 or 2.
12. A cured product of the composition according to claim 11.
Citation Information
Patent Citations
Thermally conductive silicone oil compound
JP1990212556A
Heat radiating body having high thermal conductivity and its manufacture
JP1994209057A